The link between emotion regulation and size estimation of spiders pictures among women with fear of spiders - Ben-Baruch, Yahel Dror; Leibovich-Raveh, Tali; Cohen, Noga (Frontiers in Psychology, 2022)
Introduction Fear is associated with perceptual biases. People who are afraid of spiders perceive spiders as larger than people without this fear. It is yet unclear, however, whether this effect can be influenced by using implicit (non-deliberate) emotion regulation (ER) processes and explicit (deliberate) ER strategies, such as reappraisal and suppression. Method This study examined the link between implicit and explicit ER and size estimation among women afraid of spiders. After performing an implicit ER (cognitive control) task, participants rated the size and valence of spiders, wasps and butterflies shown in pictures. Participants’ tendency to use reappraisal and suppression was assessed using the Emotion Regulation Questionnaire. Results Results showed no effect of implicit ER on size and valence ratings. A greater tendency to use reappraisal was linked to reduced negative feelings on seeing the pictures of spiders. Greater use of suppression, however, was linked to increased size estimation of the spider stimuli. Discussion These results highlight the role of ER in perceptual biases and offer avenues for future ER-based treatments for specific phobias.